Decomposing the Contribution of Migration to Poverty Reduction : Methodology and Application to Tanzania - Christiaensen, Luc (Taylor and Francis, 2019)
In an economy with migration, poverty changes are composed of a number of forces, including the income gains and losses realized by the various migration streams. We present a simple but powerful decomposition methodology that uses panel data to measure the contributions of different migration streams to overall poverty change. An application to Tanzania shows the new insights that are provided – in particular on the role of migration to secondary towns in poverty reduction.